Al rich PVD protective coatings: A promising approach to prevent T91 steel corrosion in stagnant liquid lead - Miorin, Enrico; Montagner, Francesco; Zin, Valentina; Giuranno, Donatella; Ricci, Enrica; Pedroni, Matteo; Spampinato, Valentina; Vassallo, Espedito; Deambrosis, Silvia Maria (Surface & coatings technology, 2019)
In order to investigate a protective coating approach for nuclear applications, two different aluminum rich layers were deposited on T91 steel coupons: Ti-Al-N films were grown via High Power Impulse Magnetron Sputtering and AlO coatings were produced by Radio Frequency Magnetron Sputtering. In this exploratory work, coated specimens were corrosion tested in stagnant Pb at 550 °C for 1200 h and both types of coatings proved to be effective in protecting the substrate from the harsh environment. Due to the severe experimental conditions, the Al oxide film underwent some mechanical changes, while, the nitride coating demonstrated its noteworthy stability. [Display omitted] •Assessment of Al-rich coatings potentiality against liquid lead corrosion of steel•Aluminum Oxide and Titanium Aluminum Nitride coatings by magnetron sputtering•Coated and bare samples are exposed to severe liquid lead corrosive attack.•Aluminum-rich coatings are effective in protecting steel from corrosion.•Nitride coatings maintain their excellent mechanical properties unchanged.